EVALUASI KEPUASAN PENGGUNA APLIKASI M-HEALTH COVID19 SATUSEHAT DENGAN END USER COMPUTING SATISFACTION (EUCS) DAN MOBILE SERVICE QUALITY(M-S-QUAL) - Usman Abrori; Aang Kisnu Darmawan; Muhsi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The SatuSehat application is still new and encounters problems in use. Complaints reported by the public include frequent application errors, failures at check-in, and the length of time it takes to issue vaccine certificates. Users must enter personal data to enter the application. The SERVQUAL method is used to compare service expectations and reality, while the EUCS method is used to measure user satisfaction.